2020
DOI: 10.1080/22221751.2019.1708215
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Fc-dependent cell-mediated activity of a vestigial esterase-targeting antibody against H5N6 virus infection

Abstract: The highly pathogenic avian influenza A (H5N6) virus has caused sporadic human infections with a high case fatality rate. Due to the continuous evolution of this virus subtype and its ability to transmit to humans, there is an urgent need to develop effective antiviral therapeutics. In this study, a murine monoclonal antibody 9F4 was shown to display broad binding affinity against H5Nx viruses. Furthermore, 9F4 can neutralize H5N6 pseudotyped particles and prevent entry into host cells. Additionally, ADCC/ADCP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…The variable heavy (VH; GenBank accession number: DQ168569) and variable light (VL; GenBank accession number: DQ168570) genes of CR3022 were generated by gene synthesis (Bio Basic Asia Pacific) and cloned into pFUSEss-CHIg-hIgG1 and pFUSE2ss-CLIg-hK cloning vectors (InvivoGen, San Diego, CA, United States) respectively. Transfection of suspension FreeStyle 293 cells (Thermo Fisher Scientific) and purification of antibodies by fast protein liquid chromatography is as described in our previous study [23].…”
Section: Production Of Monoclonal Antibody Cr3022mentioning
confidence: 99%
“…The variable heavy (VH; GenBank accession number: DQ168569) and variable light (VL; GenBank accession number: DQ168570) genes of CR3022 were generated by gene synthesis (Bio Basic Asia Pacific) and cloned into pFUSEss-CHIg-hIgG1 and pFUSE2ss-CLIg-hK cloning vectors (InvivoGen, San Diego, CA, United States) respectively. Transfection of suspension FreeStyle 293 cells (Thermo Fisher Scientific) and purification of antibodies by fast protein liquid chromatography is as described in our previous study [23].…”
Section: Production Of Monoclonal Antibody Cr3022mentioning
confidence: 99%
“…Effector immune cells, most commonly natural killer (NK) cells, bind to the antibodies via Fc receptors on their surface and then undergo degranulation releasing perforin and granzyme lysing infected cells. ADCC has been observed after infection with a number of viral pathogens ( Garcia et al, 2006 ; He et al, 2016 ; Singh et al, 2018 ), and it has been demonstrated to be an important component of protective immunity against HIV-1 ( Asokan et al, 2020 ; Haynes et al, 2012 ; Su et al, 2019 ), Influenza ( Gao et al, 2020b ; Zheng et al, 2020 ), Ebola ( Wagstaffe et al, 2019 ) and may have a role in other viral infection ( Chen, 2020 ). Since little is known about the role of ADCC in SARS-CoV-2 infections, we developed a functional SARS-CoV-2 spike (S) protein-based ADCC assay to assess the development and kinetics of antibodies after SARS-CoV-2 infection.…”
Section: Introductionmentioning
confidence: 99%
“…One (G225D) of the mutations is shared among the dominant subclades, and four others (E50K, F79V, I140K, and G186D) are typically encoded by viruses from the 2b subclade [55]. Notably, the G225D, I140K, and N186D are in the sialic acid binding site, and the E50K and F79V substitutions are situated in the F' and VE domains [20,[65][66][67]. Mutations within the receptor-binding domain can alter the interaction between the HA protein and alpha-2,3 or alpha-2,6 sialic acids across diverse host species [68].…”
Section: Discussionmentioning
confidence: 99%